The Role of Multilayer Electrospun Poly(Vinyl Alcohol)/Gelatin nanofibers loaded with Fluconazole and Cinnamaldehyde in the Potential Treatment of Fungal Keratitis. (5th August 2022) - Ilhan, Elif; Cesur, Sumeyye; Sulutas, Rabia Betul; Pilavci, Esra; Dalbayrak, Basak; Kaya, Elif; Arisan, Elif Damla; Tinaz, Gulgun Bosgelmez; Sengor, Mustafa; Kijeńska-Gawrońska, Ewa; Oktar, Faik Nuzhet; Gunduz, Oguzhan
Graphical abstract: Highlights: CA and FLU-loaded PVA/GEL fibers were successfully produced with electrospinning. CA layer is for to inhibit the biofilm and FLU layer provides antifungal effect. CA and FLU were released from nanofibers in a controlled release manner. Abstract: Fungal keratitis is a severe corneal infection that causes irreversible damage to the cornea, for which conventional drug treatments may be insufficient. With the new generation of drug delivery systems, it is desired to ensure the ocular usability of drugs. In this study, two-layer polyvinyl alcohol and gelatin (PVA/GEL) nanofibers with high drug loading capacity were produced by the electrospinning method. Cinnamaldehyde (CA), an FDA-approved volatile molecule found in cinnamon essential oil, and fluconazole (FLU), an antifungal drug, were incorporated into PVA/GEL nanofibers to inhibit the growth and biofilm formation of Candida albicans, one of the pathogens that cause fungal keratitis. The morphology, chemical structures, and thermal transitions of the produced pure (PVA/GEL), FLU loaded (PVA/GEL/FLU), CA loaded (PVA/GEL/CA), and combined FLU and CA loaded (PVA/GEL/COM) nanofibers were analysed by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) and differential scanning calorimetry (DSC), respectively. The mechanical analysis, swelling and degradation behaviour, and drug release kinetics of the nanofibers were investigated. PVA/GEL/FLU, PVA/GEL/CA and PVA/GEL/FLU/COM nanofibers were evaluated for their antifungal and antibiofilm activity against Candida albicans . Results showed that PVA/GEL/FLU and PVA/GEL/COM nanofibers have significant antifungal activity and inhibited biofilm formation by 37% and 49%, respectively. Furthermore, it was determined by MTT analysis using a human embryonic kidney (HEK) that the nanofibers were not cytotoxic. In the treatment of fungal keratitis, double-layer PVA/GEL/COM nanofiber with CA in the first layer and FLU in the second layer can create a new treatment approach as an alternative drug delivery system.